(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Many senior high school students often have trouble in choosing what college course to take in college, especially those who are in their senior years. It can be a difficult decision to make for teens because peers or parental pressure tends to have a huge impact on their decision at that age. Most college students become stuck with the course they do not like or particularly interested in. Given that the course they are going to take will affect the career they can eventually pursue, students should decide which course will be the best for them in advance. The researchers conducted this study to determine the factors that affect the college course selection of selected General Academic Strand students. A quantitative descriptive research design was used here. The researchers utilized purposive sampling and selected 50 Grade 12 General Academic Strand students to assess the factors that affect college course selection. Based on the table, with the weighted means of 3.85 for male respondents and 3.41 for female respondents, both groups strongly agreed that financial support is one of the factors that affect college course selection. With the weighted means of 3.73 for male respondents and 3.32 for female respondents, both groups strongly agreed that parents’ choice is one of the factors that affect college course selection. Male respondents strongly agreed, with the weighted mean of 3.11, and female respondents agreed that peer influence is one of the factors that affect college course selection, with the weighted mean of 2.95. With the overall weighted means of 3.56 for male respondents strongly agree for female respondents, both groups agreed that financial support, parent’s choice, and peer influence are the factors that affect college course selection. Based on the findings of the study and conclusions that were drawn, the following guidelines were forwarded. Students should choose their college courses wisely. Students should ask themselves why they chose a specific course, find jobs that are similar to your course, pay attention to details in their courses, consider prospective careers and employment opportunities, get scholarships, be practical, check the career prospective, talk to their employer colleagues or peers about which course are relevant, and think about which subject interests them.